Risk Mitigation of Air Knocker Using Fuzzy FMEA-AHP: A Case Study - Panudju, Andreas Tri; Sitorus, Helena; Marfuah, Umi; Sudarwati, Wiwik; Nurhasanah, Nunung (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
This research is driven by the necessity for effective and high-quality maintenance systems capable of fulfilling rigorous equipment maintenance standards. The purpose of this study was to identify potential failures in an air knocker, evaluate the risk of failure through the Fuzzy FMEA approach, and optimize decision-making using the AHP method. This study was based on theories related to maintenance, Fuzzy FMEA, and AHP. The research methodologies employed comprised a literature review, data analysis, and the application of Expert Choice software to compute weights and ratings according to pertinent criteria. The results showed that the integration of Fuzzy FMEA and AHP methods was effective in identifying potential failures, evaluating risks more accurately, and prioritizing optimal corrective actions in the maintenance system. This study suggests that the integration of Fuzzy FMEA and AHP methods can improve risk management and decision-making in maintenance systems. This strategy assists organizations in mitigating the risk of failure, enhancing efficiency, and more effectively addressing process requirements. This methodology enables a more comprehensive examination of risk variables and the efficient management of uncertainties, as well as the decision-making process for assessing the risks associated with air knocker operations.